Analisis Faktor-Faktor yang Mempengaruhi Loyalitas Tamu pada Hotel Windsor Toya, Hokkaido, Jepang: Studi Kasus dalam Perspektif Servuction Model - Gisso, Tirsa; Yuliamir, Henry (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This study aims to analyze the factors shaping guest emotional loyalty at the Windsor Toya Hotel, Japan, through a qualitative case study with thematic analysis, emphasizing the emotional dimension and personal experiences of guests. Using a qualitative approach and thematic analysis of guest narratives, the results show that loyalty is not solely dependent on the quality of physical facilities, but is primarily influenced by emotional aspects such as the personal touch of the staff, genuine interactions, an exclusive atmosphere, and the perceived prestige of the hotel. The findings indicate that loyalty is primarily influenced by the personal touch of the staff, interpersonal interactions, and the exclusive image of the hotel. The location by Lake Toya also enhances memorable guest experiences. These results confirm that emotional loyalty, not merely transactional loyalty, is key to sustainable guest relationships. This study emphasizes the importance of personalized service strategies and experience-based storytelling for luxury hotels.